Implementasi Metode Ummi Dalam Meningkatkan Kemampuan Membaca Al-Quran Peserta Didik di SDI Plus Ulul Albab Kelutan Ngronggot Nganjuk - Kumala, Akhsinatul; Arini, Aida; Umam, Khoirul; Anshori, Sholihul; Ridlwan, Burhanuddin (AL MURABBI, 2023)
This research is motivated by the phenomenon of elementary schools holding Al-Qur'an or TPQ learning activities because of the interests of the parents who want children at school to also be taught to read the Al-Qur'an, so with this the researcher wants to describe learning activities to read the Koran using the Ummi method at SDI Plus Ulul Albab. The research method in this research is qualitative research which uses observation, documentation and interview data collection.The results of the research show that the reading ability of SDI Plus Ulul Alab students has developed very well, where this achievement can be seen from student development data, namely through student achievement cards and journals. The implementation involves several stages including opening, apperception, concept planting, training/skills, closing. The inhibiting factors are limited teaching aids, lack of administrative staff, the implementation time is too late in the day and the supporting factors are the existence of adequate classrooms, the availability of teaching guidebooks from the center, demonstration books to facilitate learning completion, the teaching staff are Ummi certified Keywords: Ummi Method, Reading Ability